EFFICIENCY IMPROVEMENT OF SELF-REGULATING WIND POWER PLANTS - N.S. Buktukov; B.ZH. Buktukov; G.ZH. Moldabayeva (Academic Journal of Physical and Chemical Sciences, 2019)
The wind power plant with high coefficients of use in time and rated power has been Developed. It operates in the range of wind speeds from 2-3 to 50 m/s. The rated power is achieved depending on the design at speeds from 5-8 m/s to 50 m/s.